Students’ Perception of Using YouGlish in Learning Pronunciation of Tenth Grade of Senior High School - Reza Pitri Handayani; Rulik Setiani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to understand how students see using the YouGlish Platform to acquire English pronunciation.Thirty-four students from Senior High School's class X-3 participated. A questionnaire intended to gauge students' opinions on using YouGlish to acquire pronunciation was used to gather data for this study, which used a qualitative descriptive method.  The results showed that the majority of pupils had favourable opinions. They felt that YouGlish helped them become more confident in speaking, enriched their vocabulary in authentic contexts, improved their understanding of proper word stress and intonation, and enhanced their pronunciation accuracy. Moreover, YouGlish was considered engaging and effective for self-directed learning. However, some challenges were also identified, such as the difficulty of understanding various English accents, dependence on stable internet access, and the need for teacher guidance to use the platform effectively. In conclusion, despite these technical and instructional challenges, YouGlish remains a valuable and enjoyable digital tool that supports pronunciation learning. This study highlights the limited exploration of digital pronunciation platforms like YouGlish in the Indonesian EFL context, emphasizing its potential for enhancing pronunciation learning in future English instruction.